Oliceridine, a Novel G Protein–Biased Ligand at the μ‐Opioid Receptor, Demonstrates a Predictable Relationship Between Plasma Concentrations and Pain Relief. II: Simulation of Potential Phase 3 Study Designs Using a Pharmacokinetic/Pharmacodynamic Model. (2nd February 2018) - Fossler, Michael J.; Sadler, Brian M.; Farrell, Colm; Burt, David A.; Pitsiu, Maria; Skobieranda, Franck; Soergel, David G.
Abstract: Oliceridine is a novel G protein–biased ligand at the μ‐opioid receptor that differentially activates G protein coupling while mitigating β‐arrestin recruitment. Unlike morphine, oliceridine has no known active metabolites; therefore, analgesic efficacy is predictably linked to its concentration in the plasma. Oliceridine is primarily hepatically metabolized by CYP3A4 and CYP2D6. Using a pharmacokinetic/pharmacodynamic model relating oliceridine plasma concentrations to its effect on pain intensity as measured by numeric pain‐rating scale (NPRS) scores, we have simulated potential dosing regimens using both fixed‐dose regimens and as‐needed (prn) dosing regimens in which various doses of oliceridine were administered if NPRS scores indicated moderate to severe pain (≥4 on a 0‐10 scale). In addition, regimens in which oliceridine was self‐administered via a patient‐controlled analgesia device were also simulated. The simulated population included 10% CYP2D6 poor metabolizers (PM). The simulation results suggest that oliceridine doses of 1‐3 mg prn should be effective in reducing NPRS scores relative to placebo. The simulations also revealed that a 1‐mg "supplemental dose" given 0.25 hour after the loading dose would decrease NPRS scores further in almost one‐third of patients. In addition, if oliceridine is administered prn, a longer interval between doses is observed in simulated PM patients, consistent with their reduced oliceridine clearance. Because this longer average dosing interval is predicted to decrease oliceridine exposure in PM patients, the need to know the patient's CYP2D6 genotype for dosing is effectively obviated.